2008
DOI: 10.1289/ehp.11372
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of State Fish Consumption Advisories Targeting Sensitive Populations

Abstract: ObjectiveFish consumption advisories are issued to warn the public of possible toxicological threats from consuming certain fish species. Although developing fetuses and children are particularly susceptible to toxicants in fish, fish also contain valuable nutrients. Hence, formulating advice for sensitive populations poses challenges. We conducted a comparative analysis of advisory Web sites issued by states to assess health messages that sensitive populations might access.Data sourcesWe evaluated state advis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…We suggest dissemination of this information via brochures, pamphlets, and personal guidance from physicians. Scherer et al (2008) found that pamphlets and brochures may be especially effective at targeting sensitive populations. In those small towns and villages lacking direct access to healthcare, targeting respected community leaders who believe in and understand the possible risks associated with consuming sea turtles may be an additional means of effectively disseminating this information.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…We suggest dissemination of this information via brochures, pamphlets, and personal guidance from physicians. Scherer et al (2008) found that pamphlets and brochures may be especially effective at targeting sensitive populations. In those small towns and villages lacking direct access to healthcare, targeting respected community leaders who believe in and understand the possible risks associated with consuming sea turtles may be an additional means of effectively disseminating this information.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…While all states currently issue sport fish consumption advisories, there is little consensus as to the most effective ratio of risk‐to‐benefit information, level of detail in explaining risks, or a definition of the sensitive population. ( 28 ) Nor has the wide range of advisory formats been systematically evaluated to determine the most effective approach to reach intended audiences. States also use different definitions of portion size (i.e., the amount of fish eaten at one time).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of geographic heterogeneity across South Asian megacities may suggest that meta-analysis of omega-3 supplementation or fish consumption benefits [2], or even regionally stratified meta-analysis [1] may fail to adequately capture the local context of appropriate seafood nutritional guidance. In the U.S. and Canada, when a local fish is known to be heavily contaminated with a toxic chemical, a "fish advisory" is typically issued to discourage local consumption [37,38]. Similar principles of contextually dependent risk-benefit analysis for seafood consumption might be able to inform nutritional epidemiology in other settings.…”
Section: Discussionmentioning
confidence: 99%